2002
DOI: 10.1007/s007050200025
|View full text |Cite
|
Sign up to set email alerts
|

A novel amino acid position in hemagglutinin glycoprotein of measles virus is responsible for hemadsorption and CD46 binding

Abstract: Three recent isolates of measles virus Fu, IMA, and SMD obtained by using B95a cells did not exhibit hemadsorption with African green monkey red blood cells (AGM-RBC). After long-term passage in Vero cells, these Vero cell-adapted strains derived from three isolates obtained the activity to agglutinate AGM-RBC. The primary sequences of the hemagglutinin (H protein) and fusion glycoproteins (F protein) from these two types of viruses were compared and revealed that several important amino acid residues in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Strikingly, the revised structural model's 3D surface representation reveals (Fig. 6B and D) that the continuous site formed by D505, D507, and R533 is extended by residues T531 and R547, and this overlaps with residues 546, 548, and 549, recently identified as a second CD46 binding site in MVH (23). Although R547 resides in the center of the 546-548-549 CD46 binding site (in terms of both primary structure and tertiary structure), mutation of this residue has only a minimal effect on CD46 downregulation.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Strikingly, the revised structural model's 3D surface representation reveals (Fig. 6B and D) that the continuous site formed by D505, D507, and R533 is extended by residues T531 and R547, and this overlaps with residues 546, 548, and 549, recently identified as a second CD46 binding site in MVH (23). Although R547 resides in the center of the 546-548-549 CD46 binding site (in terms of both primary structure and tertiary structure), mutation of this residue has only a minimal effect on CD46 downregulation.…”
Section: Resultsmentioning
confidence: 90%
“…It has been known since 1996 that the MVH residue Y481 is important for attachment to CD46 (1,17,21,39), but recently, evidence that other residues can also play a role has accumulated: an MVH mutant in which five alanines replaced the 473-to-477 region was not functional in a hemadsorption assay (31), the S546G substitution has been shown to increase hemadsorption and CD46 binding (5,23), and residues S548 and F549, which are present in both wt and laboratory-vaccine MV strains, appear to represent a low-affinity CD46 binding site (27).…”
mentioning
confidence: 99%
“…Interestingly, the reference strain of genotype D2 (Johannesburg.SOA/88/1) has an asparagine at position 484 of the H protein in addition to a tyrosine at position 481, whereas that of genotype E (Goettingen.DEU/71 "Braxator") possesses glycine at positions 492 and 546 of the H protein (57). It is known that S546G substitution in the H protein, like the N481Y substitution, allows MV to use CD46; indeed, some Vero cellgrown MVs have an S546G substitution in the H protein instead of N481Y (13,14,21,24,27,32,36,37,43,46,56). Thus, these two reference strains seem to have the ability to use CD46 efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that an asparagine-to-tyrosine substitution at position 481 (N481Y) enables the H proteins of wild-type MV strains to bind CD46, without compromising their ability to use SLAM (8,12,20,58). In fact, when wild-type MV strains adapt to SLAM-negative and CD46-positive Vero cells, the N481Y substitution is often observed after several passages (21,27,43). Mutational analysis of the MV H protein, combined with its structural modeling, confirmed the importance of the tyrosine residue at position 481 in the interaction with CD46 (23,55).…”
Section: Measles Virus (Mv) a Member Of The Genus Morbillivirus In Tmentioning
confidence: 99%
“…Since these cells did not express the authentic MV receptor SLAM, viruses may have come to use alternate receptors such as CD46 by introducing changes in the H gene. In fact, all vaccine strains whose genomic sequences have been determined, as well as the Edmonston "wild-type" strain, have the changes (481Y and/or 546G) in the H protein that allow virus to bind CD46 (19,20,28,47). However, as our present study shows, even without those mutations that enable virus to enter cells efficiently, virus may be able to grow well in SLAMnegative cells by introducing changes in genes other than the H gene.…”
Section: Discussionmentioning
confidence: 99%